2004
DOI: 10.1158/0008-5472.can-04-0838
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival Mechanisms Associated with Perineural Invasion in Prostate Cancer

Abstract: Perineural invasion (PNI) is the major mechanism of prostate cancer spread outside the prostate. Apoptotic and proliferation indices were determined in PNI cells using the PNI in vitro model and human PNI in tissue microarrays. RNA was extracted from the PNI model and controls and evaluated by cDNA microarray analysis. Differential expression of candidate genes was confirmed by real-time quantitative PCR, fluorescence, and immunohistochemistry using tissue microarrays. Genistein and BAY 11-7085 were added to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
150
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(162 citation statements)
references
References 33 publications
10
150
1
1
Order By: Relevance
“…26 It is also recognized that proximity of intraprostatic tumor to the resection margin in radical prostatectomy specimens is not of prognostic significance. 27 In view of this, our finding that the presence of proximity of perineural invasion to the prostatic capsule or excision margin is not associated with a higher rate of biochemical failure implies that, while infiltration of the perineural space may promote local tumor growth, it does not necessarily facilitate extraprostatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…26 It is also recognized that proximity of intraprostatic tumor to the resection margin in radical prostatectomy specimens is not of prognostic significance. 27 In view of this, our finding that the presence of proximity of perineural invasion to the prostatic capsule or excision margin is not associated with a higher rate of biochemical failure implies that, while infiltration of the perineural space may promote local tumor growth, it does not necessarily facilitate extraprostatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…PNI diameter was obtained as previously described. 22,27 The point scores are obtained from each predictor (log preoperative PSA, lymph node status, SM, ECE, Gleason score, stroma percentage quantification of RSG 3 area as stroma percentage, and PNI diameter) and then manually tallied to obtain a total score before reading predicted recurrence-free probability. As the nomogram shows ( Figure 6), RSG 3 provides unique information to the model and the information provided has significant weight.…”
Section: Postoperative Nomogram With Pni Diameter and Quantification mentioning
confidence: 99%
“…Perineural invasion (PNI), commonly found in PCa, is a hosttumor interaction between nerves and cancer cells that leads to costimulation of growth. [22][23][24][25][26] Cancer cells grow more when around the nerve and also induce neurogenesis in an autocrine loop. 27 We previously demonstrated that PNI diameter, a measure of tumor diameter around the nerve, is also a very strong biomarker for BCR-free survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven genes were overexpressed, whereas 18 were significantly reduced in association with the acquisition of a metastatic capability during in vivo selection of LNM35 (Table 1). The 27 examples overexpressed in LNM35 included various genes previously suggested to play a functional role in metastasis such as chemokine (C-X-C motif) ligand (Heaney et al, 2000;Bernal et al, 2002), immediate early response 3 (IER3) (Goswami et al, 2004;Nicholson et al, 2004), defender against cell death 1 (DAD1) (Ayala et al, 2004;Goswami et al, 2004;Kim et al, 2006) and methionyl aminopeptidase 2 (METAP2) (Dasgupta et al, 2005;Morowitz et al, 2005). Similarly, genes with higher expression in N15 also included some previously implicated in metastasis such as cadherin 1 (E-cadherin) (Cavallaro and Christofori, 2004) and lectin galactoside-binding soluble 3 (galectin-3) (Liu and Rabinovich, 2005).…”
Section: Identification Of Genes Associated With the Acquisition Of Mmentioning
confidence: 99%